MENGUNGKAP PRAKTIK SENJANGAN ANGGARAN PADA ORGANISASI NIRLABA: BADAN PENGELOLA DANA AMANAT (STUDI ETNOMETODOLOGI) - Tsani Aji Novarima; Unti Ludigdo; Yeney W. Prihatiningtias (Jurnal Akuntansi Aktual, 2018)
The purpose of this study is to understand how budgetary slack occurs in operational funds of the Badan Pengelola Dana Amanat which is a non-profit organization. This research uses qualitative research method interpretive with etnometodology approach. Data collection was conducted through interviews with key informants who have roles in the Tim Penyusun Rencana Kerja Anggaran Tahunan (RKAT). The results show that budgetary participation in the process of budgeting operational funds encourages individuals to commit budgetary slack. Budgetary slack are made by individuals by targeting lower membership coverage than actual potential, and calculating higher operational costs than necessary ones. This study proves that non-profit organizations are not sterile from budgetary slack.Keywords:Budgetary participation; budgetary slack; ethnometodology; Badan Pengelola Dana Amanat